Perancangan Interior Pusat Komunitas Penggemar Kue di Surabaya - Lucky Basuki, Natalia Hidayat Yusita Kusumarini (Intra, 2013)
The definition of interior design is to design a community center that is used to place a particular community gathering place. This is the appointed time fan community in Surabaya cake. Food is the main business promising, because everyone can not be separated from the feed. As more and more types of cakes that have sprung up, ranging from the long-known cake until the cake you just met, it would be nice if the fans of light snacks that is cakes are also know what and where they eat the cake. Expected by the community centers interior, can provide a container to gather, explore ideas, gain new experiences and obtain useful information between the members of the cakeâs fan community in Surabaya.